Hacking the hacker :blearn from the experts who take down hackers - Grimes, Roger A.,eauthor (ITpro collection, 2017)
Meet the world's top ethical hackers and explore the tools of the trade Hacking the Hacker takes you inside the world of cybersecurity to show you what goes on behind the scenes, and introduces you to the men and women on the front lines of this technological arms race